1991
DOI: 10.1007/bf00401327
|View full text |Cite
|
Sign up to set email alerts
|

Non-radiological contaminants from uranium mining and milling at Ranger, Jabiru, Northern Territory, Australia

Abstract: Protection from the hazards from radioactivity is of prime importance in the management of uranium mine and mill wastes. Such wastes also contain non-radiological contaminants (heavy metals, acids and neutralising agents) which give rise to potential long-term health and environmental hazards and short-term hazards to the aquatic ecosystem, e.g. as a result of release of waste water. This study seeks to identify non-radiological contaminants (elements) transferred to waste water at the Ranger uranium mine/mill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…The relative proportions of these three uranyl-organic species progressively decline with increasing uranyl concentration, ranging from approximately 83% at background to about 21% at 4 mg 1 1 . In contrast to pH 5, the relative proportions of the hydrolysed uranyl-organic species (i.e.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The relative proportions of these three uranyl-organic species progressively decline with increasing uranyl concentration, ranging from approximately 83% at background to about 21% at 4 mg 1 1 . In contrast to pH 5, the relative proportions of the hydrolysed uranyl-organic species (i.e.…”
Section: Resultsmentioning
confidence: 97%
“…Uranium has been identified as the prime ecotoxic contaminant in mine waste waters [1] entering the Magela Creek, downstream of the Ranger Uranium Mine (RUM), Alligator Rivers Region, Northern Australia (12°40'S, 132°57'E) (see Fig. 1 in Brown et al [2]).…”
Section: Introductionmentioning
confidence: 98%
“…However, the higher levels of Ln have also been reported: sum Ln concentrations in the Syr Darya River ranged from 15.1-28.3 µg/L [118] and concentrations of Ln in stream waters (Eastern Canada) from <5 to 11,540 ng/L, with an average of 253 ng/L (n = 498) [119]. At very polluted sites, Ln concentrations may increase up to 78 µg/L [114,120] and, in exceptional cases, e.g., in acid mine drainage waters or after lake restoration while using Ln-modified bentonite clay, Ln concentrations may even reach 15 mg/L [116,[121][122][123][124][125]. Thus, comparison of the Ln concentration in the surface waters and reported toxicity values allows for concluding that, although even in contaminated waters Ln concentrations are still lower than the reported toxic concentrations for aquatic organisms, in certain cases (e.g., in the treated water bodies or mine waste water) Ln may already disturb normal function of ecosystem.…”
Section: Environmental Exposure Levels Of Lnmentioning
confidence: 99%
“…The low toxicity of Mg under most environmental conditions and its role in ameliorating the toxicity of more toxic transition metals has meant that it has rarely been considered a priority environmental toxicant [7]. However, Mg has been identified as a contaminant of concern in mine waters that are discharged from the Ranger Uranium Mine in northern Australia [7][8][9]. Site-specific ecotoxicological testing confirmed that Mg was more toxic than in previous Mg studies in the extremely soft waters surrounding Ranger Mine.…”
Section: Introductionmentioning
confidence: 93%